TINJAUAN YURIDIS TERHADAP PENGELOLAAN ASET-ASET GAMPONG (Studi Kasus Gampong Paya Baro Kabupaten Aceh Jaya) - Sari Yulis; Handoyo, Budi; Friwarti, Sri Dwi (Prodi Hukum Tata Negara Islam (Siyasah Syar'iyyah) STAIN Teungku Dirundeng Meulaboh, 2024)
Gampong assets are items belonging to the gampong that originate from the Gampong's original assets, purchased or obtained at the expense of the Gampong Revenue and Expenditure Budget (APBG) or the acquisition of other legal rights. The purpose of this research problem formulation is (1) to find out how the assets of Gampong Paya Baro are managed, and (2) to find out how effective the management of Gampong Paya Baro's assets is in terms of the juridical aspect in managing the assets of Gampong Paya Baro. This research uses qualitative field research methods. The types of data in this research are secondary data (library) and primary data (field). Data collection techniques are interviews and documentation. Data processing and analysis techniques include data reduction, data presentation, drawing conclusions and guidelines for writing a thesis. Based on the results of this research (1) the assets of Gampong Paya Baro consist of oil palm plantations, Kede-kede Gampong, Hand Tractors, Fish Shelters, Rice Threshers, and Teratak along with Chairs. The management of the assets of Gampong Paya Baro, Teunom District, Aceh Jaya Regency has not been fully implemented using Transparency (openness, honesty and clarity), Accountability (Responsibility), and Participation (cooperating) carried out by the gampong government and the Gampong Paya Baro community. (2) The effectiveness of the management of gampong assets is reviewed from a juridical aspect, Aceh Jaya Regency Qanun Number 4 of 2018 concerning Gampong Government states that the management of gampong assets is the authority of the Keuchik to gampong officials. Based on this Qanun, the effectiveness of managing the assets of Gampong Paya Baro has not been carried out effectively